Learning Infrastructure Facilities for Physical Education, Sports and Health Public Elementary Schools (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
This research aims to determine the infrastructure of learning physical education, sports, and health of Public Elementary School in Parakan District, Temanggung Regency. The research method used is descriptive qualitative by describing the state of infrastructure facilities for physical education, sports and health learning in schools. The data collection technique of this research uses observation, interview, and documentation techniques. Quantitative data obtained through observation, interview and documentation techniques were analyzed and then converted to qualitative data. The subjects of this research were Public Elementary School in Parakan District, Temanggung Regency, totaling 22 schools. The results showed that the infrastructure facilities for learning physical education, sports and health of Public Elementary School in Parakan District, Temanggung Regency were in good category of 2 schools (9.09%), in enough category were 9 schools (40.91%) and less in 11 schools (50%). The results of this research concluded that infrastructure facilities learning physical education, sports, and health of public elementary schools in Parakan District, Temanggung Regency in the average category fulfilled RI Minister of Education Regulation No. 24 of 2007 concerning infrastructure facilities standards and has been implemented with the policy direction of the school.